Let $$f(z) = \sum_{k=0}^{n}c_{k}z^{k}$$ be a polynomial, where $c_{k}\in\mathbb{C}$.

Prove that

$$\int_{-1}^{1}|f(x)|^{2}dx\leq\pi\int_{0}^{2\pi}|f(e^{i\theta})|^{2}\frac{d\theta}{2\pi} = \pi\sum_{k=0}^{n}|c_{k}|^{2}$$

I tried letting $c_{k} = a_{k}+ib_{k}$ for real $a_{k},b_{k}$ and got to $$\int_{-1}^{1}|f(x)|^{2}dx = \int_{-1}^{1}\left(\sum_{k=0}^{n}a^{k}x^{k}\right)^{2}+\left(\sum_{k=0}^{n}b^{k}x^{k}\right)^{2}dx$$ but I'm not sure how to go from here. Am I on the right track (if so can you outline the next few steps?) or should I be approaching this another way?

What I know;

  • In the previous part of the question I proved for real $c_{k}$ $$\int_{-1}^{1}[f(x)]^{2}dx\leq\pi\int_{0}^{2\pi}|f(e^{i\theta})|^{2}\frac{d\theta}{2\pi} = \pi\sum_{k=0}^{n}c_{k}^{2}$$ using the Cauchy Theorem and two integrals around the uppper/lower unit semicircles:

Proof (if helpful) Consider the counter-clockwise contour from traversing the real axis from $(-1,0)$ to $(1,0)$, and then a semicircle of radius 1 from $(1,0)$ to $(-1,0)$. By the Cauchy Theorem the integral is $0$ as $f$ is holomorphic everywhere, so splitting the integrals into one along the real axis and one along the arc gives: $$\int_{-1}^{1}[f(x)]^{2}dx = -\int_{0}^{\pi}ie^{i\theta}[f(e^{i\theta})]^{2}d\theta$$

Now since $f$ is real valued if $c_{k}\in\mathbb{R}$, $|f|^{2}\geq 0$, so $$\int_{-1}^{1}[f(x)]^{2}dx = \left|\int_{-1}^{1}[f(x)]^{2}dx\right| = \left|-\int_{0}^{\pi}ie^{i\theta}[f(e^{i\theta})]^{2}d\theta\right|\leq \int_{0}^{\pi}|f(e^{i\theta})|^{2}d\theta$$

Similarly by considering the contour traversing the real axis from $(1,0)$ to $(-1,0)$ and then along the semicircle of radius 1 from $(-1,0)$ to $(1,0)$, we get $$\int_{-1}^{1} [f(x)]^{2}dx\leq \int_{\pi}^{2\pi}|f(e^{i\theta})|^{2}d\theta $$ Adding the two then gives the equality $$\int_{-1}^{1}[f(x)]^{2}dx\leq\pi\int_{0}^{2\pi}|f(e^{i\theta})|^{2}\frac{d\theta}{2\pi} = \pi\sum_{k=0}^{n}c_{k}^{2}$$ - I know how to prove the equality $$\pi\int_{0}^{2\pi}|f(e^{i\theta})|^{2}\frac{d\theta}{2\pi} = \pi\sum_{k=0}^{n}|c_{k}|^{2}$$

Here is the full question for reference; (note I only need help for the second part)

  • 1
    $\begingroup$ Can you show us how you proved the first part? $\endgroup$ – Yadati Kiran Nov 24 '18 at 9:43
  • $\begingroup$ Okay, I just attached a proof of the first part if it helps $\endgroup$ – BaroqueFreak Nov 25 '18 at 0:14

Write $c_k=a_k+\text{i}b_k$ for $k=0,1,2,\ldots,n$, where $a_k,b_k\in\mathbb{R}$. Then, $$f(z)=g(z)+\text{i}\,h(z)\,,$$ where $g(z):=\sum\limits_{k=0}^n\,a_k\,z^k$ and $h(z):=\sum\limits_{k=0}^n\,b_k\,z^k$ are polynomials with real coefficients.

Note that, for $x\in\mathbb{R}$, $$\big|f(x)\big|^2=\big(g(x)\big)^2+\big(h(x)\big)^2\,.$$ Applying Part (a) of the question, you get $$\int_{-1}^{+1}\,\big(g(x)\big)^2\,\text{d}x\leq \pi\,\sum_{k=0}^n\,a_k^2$$ and $$\int_{-1}^{+1}\,\big(h(x)\big)^2\,\text{d}x\leq \pi\,\sum_{k=0}^n\,b_k^2\,.$$ Adding the two inequalities above yields $$\int_{-1}^{+1}\,\big|f(x)\big|^2\,\text{d}x\leq \pi\,\sum_{k=0}^n\,|c_k|^2\,.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.